Using story reading and explicit instruction in the vocabulary acquisition of kindergarten children - Singzon, Pamela D.; Pado, Felicitas E. (2011)
This research investigated the relationship of children's literature with vocabulary acquisition of kindergarten children. A quasi-experimental study was conducted involving three kindergarten classes, with a proportionate number of boys and girls, from a public school in Quezon City. Filipino was the first language of most of the subjects. The medium of instruction used in the study was predominantly English.

The first group was exposed to Method 1 (story reading with unlocking of difficulty activities), the second group to Method 2 (story reading without unlocking of difficulty vocabulary) and the third group to Method 3 (explicit instruction in vocabulary without story reading). A pre-test and post-test was given prior to and after the vocabulary acquisition sessions. Results show that Method 1 was the most effective in contributing to the vocabulary development of the kindergarten subjects. Method 2 came in second while the least effective method was Method 3.

Independent samples and t-tests were computed to determine differences in vocabulary mean scores between boys and girls, and with the educational background of the subjects' mothers. Results showed no significant differences or interactions in both instances.
Keywords: Children's literature; Storytelling; Vocabulary -- Study and teaching; Direct instruction